1973
DOI: 10.1104/pp.51.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Starch Synthetase, Phosphorylase, ADPglucose Pyrophosphorylase, and UDPglucose Pyrophosphorylase in Developing Maize Kernels

Abstract: Soluble ADPglucose-az-glucan 4-a-glucosvltransferase (starch synthetase), ADPglucose pyrophosphorylase, UDPglucose pyrophosphorylase and phosphorylase were assayed in extracts from developing kernels of maize (Zea mays). Normal, waxy and amylose-extender maize at stages of development ranging from 8 days to 28 days after pollination were studied. Shrunken-4 maize at the 22-day stage was also studied. There is adequate activity of both ADPglucose pyrophosphorylase and starch synthetase at all stages of developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
41
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 17 publications
8
41
0
Order By: Relevance
“…In growing tissues, sugars accumulate into vacuoles (9) and contribute to osmotic water potential, thus facilitating water flow into expanding cells (1). We observed that apical kernels had substantially lower sucrose concentrations and slightly higher glucose concentrations than basal kernels during the cell expansion stage (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Similar differences in the sucrose concentration of endosperm from apical and middle-position kernels have been reported recently for field-grown maize (23).…”
Section: Materiails and Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…In growing tissues, sugars accumulate into vacuoles (9) and contribute to osmotic water potential, thus facilitating water flow into expanding cells (1). We observed that apical kernels had substantially lower sucrose concentrations and slightly higher glucose concentrations than basal kernels during the cell expansion stage (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Similar differences in the sucrose concentration of endosperm from apical and middle-position kernels have been reported recently for field-grown maize (23).…”
Section: Materiails and Methodsmentioning
confidence: 81%
“…4). Ozbun et al (11) reported that the ADPG-PPase and starch synthase activities in normal genotypes of maize endosperm were 4 to 8 and 2 to 8 times greater, respectively, than the rate of starch synthesis during the period of rapid starch accumulation. Although ADPG-PPase from maize endosperm is relatively insensitive to regulation by D-glycerate-3-P and Pi (4,26), it is possible that the current assays underestimated its potential activity due to incomplete extraction, presence of inhibitors (7), incomplete activation, or other factors.…”
Section: Materiails and Methodsmentioning
confidence: 99%
“…While the sequences of the maize SSIIa and SSIIb cDNAs have been published, the localization of the proteins they encode has not been defined (Imparl-Radosevich et al, 1999). Two isoforms of SS (originally designated SSI and SSII in order of elution from anion-exchange chromatography) have been described in soluble extracts of maize endosperm (Ozbun et al, 1973;Pollack and Preiss, 1980). It is now established that these isoforms are encoded by the SSI and dull1 genes, respectively (Harn et al, 1998;ImparlRadosevich et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Starch synthase activities often appear limiting to the starch accumulation rate in tissues such as maize endosperm (Ozbun et al, 1973) and pea embryo (Edwards et al, 1988;see Kruger, 1990). With regard to ADP-Glc PPase, transgenic potato tubers (Stark et al, 1992) and tomato fruit (Stark et al, 1996) with a nonallosterically controlled ADP-Glc PPase enzyme had increased starch levels, indicating that the in vivo flux through this step in biosynthesis is limiting to starch synthesis.…”
Section: Discussionmentioning
confidence: 99%